1987
DOI: 10.1007/bf01656593
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal function after total gastrectomy and possible consequences of gastric replacement

Abstract: About half of the patients subjected to total gastrectomy experience weight loss. Malabsorption, particularly fat malabsorption, is a common feature after total gastrectomy. This may be due to shortened intestinal transit time and small bowel bacterial overgrowth, but is less often due to diarrhea or pancreatic exocrine insufficiency. Malabsorption is not closely related to weight loss, which is mainly caused by recurrent malignant diseases and a low postoperative calorie intake. The low calorie intake persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1
4

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
1
34
1
4
Order By: Relevance
“…Pancreatico-cibal asynchrony, leading to increased fat loss and impaired weight gain, may add to the problem after Billroth II or other duodenal bypassing operations [9]. One of the most significant and prevalent pathophysiological conditions which may result in malabsorption is bacterial overgrowth in the small intestine [10]. The incidence of significant bacterial overgrowth in patients following Billroth II operations has been estimated to be 30–50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatico-cibal asynchrony, leading to increased fat loss and impaired weight gain, may add to the problem after Billroth II or other duodenal bypassing operations [9]. One of the most significant and prevalent pathophysiological conditions which may result in malabsorption is bacterial overgrowth in the small intestine [10]. The incidence of significant bacterial overgrowth in patients following Billroth II operations has been estimated to be 30–50%.…”
Section: Discussionmentioning
confidence: 99%
“…The most common secondary manifestations are vitamin B 12 malabsorption and fat malabsorption, which may result in deficiencies of the fat-soluble vitamins. Normal motility and gastric acid output are the primary factors suggested for determining normal levels of small intestinal bacteria [10]. …”
Section: Discussionmentioning
confidence: 99%
“…toms characterized by symptoms of early satiety, epigastric discomfort, nausea, and vomiting [1]. Reduction in calorie intake due to loss of stomach volume appears to be the single most important determinant of weight loss post-gastrectomy [2,3].…”
mentioning
confidence: 99%
“…Borchard (1990) reported that the autopsy confirmation of the frequency and localization of the metastatic spread of gastric cancer was to the liver in 34.3% -54.3% and to the peritoneum in 17.0% -28.4% in the world literature. Moreover, about half of all patients subjected to total gastrectomy experience weight loss, malabsorption (particularly of fat absorption), after TG (Olbe and Lundell, 1987).…”
Section: Discussionmentioning
confidence: 99%